(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2022)
We analyse an Iberian inscription made on the outer surface of a goblet of Iberian pottery. Despite the lack of stratigraphical context, the inscription was probably made before the destruction of the town at the end of the third century BC. The most notable element of the text is baika, which almost always appears in the baikar form, and exclusively in small recipients for liquids associated with worship activities. A possible epigraphic parallel for baikar could be the Latin element pocolom, ‘cup’, which appears exclusively in votive inscriptions associated with the name of the deity, which in this case could be kuni, if the parallel is correct. Another interesting element of this inscription is kutan, which could be related to the kutun / kutur pair, of also plausible religious context.